2005
DOI: 10.1074/jbc.m409444200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p70S6K in Hepatic Stellate Cell Collagen Gene Expression and Cell Proliferation

Abstract: During fibrosis the hepatic stellate cell (HSC) undergoes a complex activation process characterized by increased proliferation and extracellular matrix deposition. The 70-kDa ribosomal S6 kinase (p70S6K) is activated by mitogens, growth factors, and hormones in a phosphatidylinositol 3-kinase-dependent manner. p70S6K regulates protein synthesis, proliferation, and cell cycle control. Because these processes are involved in HSC activation, we investigated the role of p70S6K in HSC proliferation, cell cycle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
89
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 64 publications
(87 reference statements)
10
89
1
Order By: Relevance
“…5C). It has been reported that p70 S6K /S6 deletion suppresses cell proliferation in different types of cells, [40][41][42] consistent with our results in vitro. However, hepatic suppression of p70 S6K by deletion of PDK1 did not suppress hepatocyte proliferation after PH.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…5C). It has been reported that p70 S6K /S6 deletion suppresses cell proliferation in different types of cells, [40][41][42] consistent with our results in vitro. However, hepatic suppression of p70 S6K by deletion of PDK1 did not suppress hepatocyte proliferation after PH.…”
Section: Discussionsupporting
confidence: 82%
“…6 It has therefore been suggested that "survival signals" such as Akt, p70 S6K , and mTOR may be responsible for the acute response in post-PH liver regeneration, possibly by regulating cell growth and thus may contribute to the initiation and maintenance of liver regeneration when the mitotic response is impaired. 6 Conversely, p70 S6K /S6, for example, is suggested to be involved in cell proliferation [40][41][42] and post-PH liver regeneration. 42 So far, the involvement and the roles of these proteins in cell proliferation and cell growth in liver regeneration have not been well delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not currently licensed for use in liver transplantation (LT) in Europe or the United States, sirolimus is becoming more widely used in liver transplant recipients with complications of CNI therapy, particularly those with renal impairment. Other proposed benefits of sirolimus in LT include its putative antitumor properties for the management of patients transplanted for hepatocellular carcinoma 1 and its potential ability to attenuate graft injury in patients with hepatitis C. 2,3 Sirolimus, like other immunosuppressive agents, has a broad side-effect profile. 4 However, of particular concern is the increasingly recognized problem of sirolimus-induced pneumonitis, which is a well-described and potentially serious complication in renal transplantation.…”
mentioning
confidence: 99%
“…Meanwhile, p70S6K regulates protein synthesis and proliferation, and the blocking of mTOR (its upstream kinase) has been shown to inhibit DNA synthesis and Cyclin D1 expression in HSCs [10] . Our results showed that Withagulatin A decreased Akt, mTOR, and p70S6K phosphorylation levels, thereby indicating that the Akt/mTOR/p70S6K signaling pathway may at least be partially accountable for the inhibitory effect of Withagulatin A on HSC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is a master regulator of protein synthesis and activates p70 ribosomal protein S6 kinase (p70S6K), which promotes protein translation [9] . Accordingly, inhibition of the mTOR/p70S6K pathway leads to reduced HSC proliferation [10] , which might serve as a potential anti-fibrotic strategy. Type I collagen is a heterotrimer composed of two α1 chains and one α2 chain and is the prototypic constituent of the fibril-forming matrix in fibrotic liver.…”
Section: Introductionmentioning
confidence: 99%